Outlawed: Extraordinary Rendition, Torture and Disappearances in the 'War on Terror' - Caldwell, Gillian (USA; Witness, 2006)
"Outlawed" lifts the veil on extraordinary rendition through the harrowing stories of two men, places the post-9/11 phenomenon of the "war on terror" in a human rights context.
Verzio Film Festival Submission
Keywords: Documentary films